Performance of an Air-Cooled Heat Exchanger in a Separation Unit Based on Fouling Factor and Pressure Drop - Ni'mah, Kamilah Pathun; Fitriah, Fitriah; Sari, Dessy Agustina (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2023)
Heat exchangers transfer heat from a high temperature to a low temperature in a fluid. Air-cooled heat exchangers are one of the most widely used types of heat exchangers, after shell and tube heat exchangers. Its performance is determined by calculating the fouling factor value and the pressure drop. The purpose of this case study is to evaluate the performance of a water-cooled heat exchanger in a plant that produces a thickening agent (CMC, or carboxymethylcellulose), which affects the amount of ethanol produced. Ethanol will cool from 79.347 to 54.133 oC, and air will cool from 31.333 to 59.667 oC as the cold fluid. The calculation results show that both reviews exceed the design threshold of 0.007056 h.ft2.oF/Btu. These heat exchangers require maintenance and repair. These results differ from the pressure drop values on the air side and pipe section, which are 1.2.10-3 inH2O and 0.647 psia, respectively. Both values remain outside the allowable limits. The performance evaluation of process equipment in the separation unit was aided by field data. The review of the data was able to predict a plant shut-down. This action was able to effect a partial or total plant shut-down due to fouling and scale exceeding design data thresholds.